Technological Design Considerations for Home-based Health care. (July 2015) - Ing, William JZ; Summers, Ron
The aim of this paper is to investigate the technological feasibility of integrating e-health solutions as an aid to the health monitoring of patients in their own homes. The approach taken to this task is based on system engineering from which models are produced to indicate how home-based health care may be envisaged. The model outputs indicate that electronic health methods and its associated technologies offer a future where health care remains affordable.